The Influence of Employee Age on the Perception of the Components of a Pro-efficiency Organisational Climate - Wziątek-Staśko, Anna; Krawczyk-Antoniuk, Olena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The article verifies the pro-efficiency model of organisational climate and presents the results of an analysis of the relationship between its parameters, assuming the employee’s age as a moderating variable. Research Design & Methods: Literature studies and empirical research using both quantitative and qualitative methods were done. Findings: The empirical research shows a correlation between the age of employees and their perception of the components of a pro-efficiency organisational climate. Implications / Recommendations: The components of the organisational climate highlighted in the model are correlated with selected parameters for the assessment of organisational effectiveness, and people of different ages perceive them differently. Contribution: The key value of the article is its examination of the impact of selected components of organisational climate on selected parameters of organisational effectiveness, in the opinion of people of different ages. The results of the research made it possible to identify the respondents’ various preferences, taking into account the moderating variable. This issue is important for science and management staff thanks to the benefits it promises organisations.